Pulmonary evaluation of whole-body inhalation exposure of polycarbonate (PC) filament 3D printer emissions in rats - Farcas, Mariana T.; McKinney, Walter; Mandler, W. Kyle; Knepp, Alycia K.; Battelli, Lori; Friend, Sherri A; Stefaniak, Aleksandr B.; Service, Samantha; Kashon, Michael; LeBouf, Ryan F.; Thomas, Treye A.; Matheson, Joanna; et al. (Journal of Toxicology and Environmental Health, Part A, 2024)
During fused filament fabrication (FFF) 3D printing with polycarbonate (PC) filament, a release of ultrafine particles (UFPs) and volatile organic compounds (VOCs) occurs. This study aimed to determine PC filament printing emission-induced toxicity in rats via whole-body inhalation exposure. Male Sprague Dawley rats were exposed to a single concentration (0.529 mg/m 3 , 40 nm mean diameter) of the 3D PC filament emissions in a time-course via whole body inhalation for 1, 4, 8, 15, and 30 days (4 hr/day, 4 days/week), and sacrificed 24 hr after the last exposure. Following exposures, rats were assessed for pulmonary and systemic responses. To determine pulmonary injury, total protein and lactate dehydrogenase (LDH) activity, surfactant proteins A and D, total as well as lavage fluid differential cells in bronchoalveolar lavage fluid (BALF) were examined, as well as histopathological analysis of lung and nasal passages was performed. To determine systemic injury, hematological differentials, and blood biomarkers of muscle, metabolic, renal, and hepatic functions were also measured. Results showed that inhalation exposure induced no marked pulmonary or systemic toxicity in rats. In conclusion, inhalation exposure of rats to a low concentration of PC filament emissions produced no significant pulmonary or systemic toxicity.